Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.50
|View full text |Cite
|
Sign up to set email alerts
|

On learning and representing social meaning in NLP: a sociolinguistic perspective

Abstract: The field of NLP has made substantial progress in building meaning representations. However, an important aspect of linguistic meaning, social meaning, has been largely overlooked. We introduce the concept of social meaning to NLP and discuss how insights from sociolinguistics can inform work on representation learning in NLP. We also identify key challenges for this new line of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Language ideologies have an important, but often unacknowledged, influence on the development of NLP technologies (Blodgett et al, 2020). For example, an ideology that distinguishes between standard and non-standard language variations surfaces in text normalization tasks (van der Goot et al, 2021), which tend to strip documents of pragmatic nuance (Baldwin and Chai, 2011) and social signals (Nguyen et al, 2021). Language on the Internet has been historically treated as a noisy variant of English, even though lexical variation on the Internet is highly communicative of social signals (Eisenstein, 2013), and varies considerably along demographic variables (Eisenstein et al, 2014) and community membership (Lucy and Bamman, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Language ideologies have an important, but often unacknowledged, influence on the development of NLP technologies (Blodgett et al, 2020). For example, an ideology that distinguishes between standard and non-standard language variations surfaces in text normalization tasks (van der Goot et al, 2021), which tend to strip documents of pragmatic nuance (Baldwin and Chai, 2011) and social signals (Nguyen et al, 2021). Language on the Internet has been historically treated as a noisy variant of English, even though lexical variation on the Internet is highly communicative of social signals (Eisenstein, 2013), and varies considerably along demographic variables (Eisenstein et al, 2014) and community membership (Lucy and Bamman, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Some of the issues detailed in this paper may be attributed to a lack of language understanding, especially the social meaning of language (Hovy & Spruit, 2016;Flek, 2020;Hovy & Yang, 2021;Nguyen et al, 2021). See for example the discussion of the YEA-SAYER (ELIZA) EFFECT in §1.…”
Section: Natural Language Understandingmentioning
confidence: 99%
“…Although lexical normalization potentially removes social signals (Nguyen et al, 2021), it has also been shown to boost many downstream NLP tasks, including named entity recognition (Schulz et al, 2016;Plank et al, 2020), POS tagging (Derczynski et al, 2013;Schulz et al, 2016; Zupan et al, 2019), dependency and constituency parsing (Baldwin and Li, 2015;van der Goot et al, 2020;van der Goot and van Noord, 2017), sentiment analysis (Van Hee et al, 2017;Sidarenka, 2019, pp. 79, 122), and machine translation (Bhat et al, 2018).…”
Section: Definition -Lexical Normalizationmentioning
confidence: 99%